Production Management in the Short Film Menunggu Dijemput: Collaboration Between BM Production and Phylosopicture - Syahida Fatma Afifi; Filosa Gita Sukmono; Dhimas Aryo Vipha Ananda (Jogjakarta Communication Conference (JCC), 2026)
Production management is an important aspect in the making of short films, which requires efficiency in terms of time, resources, and structured work coordination. Cross-production house collaboration also requires effective work management so that the production process can run optimally. This study analyzes the application of production management in the collaborative work process across production houses in the short film Menunggu Dijemput by BM Production and Phylosopicture. The method used is qualitative with a descriptive approach through case studies. Data collection was conducted through in-depth interviews with producers and directors as well as documentation studies related to the film production process. The analysis focused on the pre-production, production, and post-production stages using a production management framework and POAC theory (Planning, Organizing, Actuating, and Controlling). The results of the study indicate that the application of production management in cross-production house collaboration plays a role in regulating work coordination, task distribution, and resource management during the short film production process, while also requiring flexibility in addressing challenges such as differences in team locations, communication systems, and limited resources.